2015
DOI: 10.1016/s2095-3119(14)60899-6
|View full text |Cite
|
Sign up to set email alerts
|

Current status of genetic transformation technology developed in cucumber (Cucumis sativus L.)

Abstract: Genetic transformation is an important technique for functional genomics study and genetic improvement of plants. Until now, Agrobacterium-mediated transformation methods using cotyledon as explants has been the major approach for cucumber, and its frequency has been up to 23%. For example, significantly enhancement of the transformation efficiency of this plant species was achieved from the cotyledon explants of the cultivar Poinsett 76 infected by Agrobacterium strains EHA105 with efficient positive selectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 70 publications
1
41
0
Order By: Relevance
“…However, the exact functions and biological significance of these TPS genes in cucumber will need to be elucidated by gain-or loss-offunction approaches like those used in model plants such as Arabidopsis (Tholl et al, 2005). Recently reported transformation protocols for cucumber should facilitate the investigation of the enzymatic hypotheses generated from this study (Nanasato et al, 2013;Wang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, the exact functions and biological significance of these TPS genes in cucumber will need to be elucidated by gain-or loss-offunction approaches like those used in model plants such as Arabidopsis (Tholl et al, 2005). Recently reported transformation protocols for cucumber should facilitate the investigation of the enzymatic hypotheses generated from this study (Nanasato et al, 2013;Wang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In general, target genes are transferred into dicotyledonous plant genomes using the Agrobacterium-mediated transformation approach (Wang et al, 2015). Success of Agrobacterium-mediated transformation depends upon the regeneration frequency and number of shoots, which, in turn, depend upon the explant types, pre-cultivation time, acetosyringone concentration, infection time and cocultivation time.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, genetic engineering has some clear advantages such as a short breeding time and no changes in the desirable characteristics of plants, therefore, it is particularly valuable in genetic improvement of cucumber (Wang et al, 2015). During the last three decades, cucumber transformation techniques have undergone advances.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, multiple shoots developed on BA-containing media failed to elongate in the same medium. This result additionally suggested that genotype is considered as one of the main factors influencing the shoot bud regeneration rate and various genotypes needed different growth regulator combinations for plantlet development (Wang et al, 2015). The number of multiple shoots was enhanced in a medium supplemented with BA alone and/or in combination with a lower dose of auxins to the highest value of 94%.…”
Section: Effect Of Ms Strength and Ga 3 Concentration On Shoot Elongamentioning
confidence: 87%